Discovery of Near-Infrared Heptamethine Cyanine Probes for Imaging-Guided Surgery in Solid Tumors - Lin, Qiao; Li, Changsheng; Wang, Yuhua; Zhu, Yanqing; Gu, Yueqing (Journal of medicinal chemistry, 2024)
Near-infrared (NIR) fluorescence imaging has attracted much attention in image-guided interventions with unique advantages. However, the clinical translation rate of fluorescence probes is extremely low, primarily due to weak lesion signal contrast and poor specificity. To address this dilemma, a series of small-molecule near-infrared fluorescence probes have been designed for tumor imaging. Among them, YQ-04-03 showed notable optical stability and remarkable sensitivity toward tumor targeting. Moreover, within a specific concentration and time range against oxidizing reducing agents and laser, it demonstrated better stability than ICG. The retention time of YQ-04-03 in tumors was significantly longer compared to other nonspecific uptake sites in the subjects, and its tumor-to-normal tissue ratio (TNR) outperformed ICG. Successful resection of in situ hepatocarcinoma and peritoneal carcinoma was achieved using probe imaging guidance, with the smallest visual lesion resected measuring approximately 1 mm3. Ultimately, this probe holds great potential for advancing tumor tracer.